Research in the history of economic thought and methodology : including a selection of papers presented at the 2019 ALAHPE Conference - Fiorito, Luca; Scheall, Scott; Suprinyak, Carlos Eduardo (Emerald Publishing Limited, 2021)
Volume 39A of 'Research in the History of Economic Thought and Methodology' features a selection of essays presented at the 2019 Conference of the Latin American Society for the History of Economic Thought (ALAHPE), edited by Felipe Almeida and Carlos Eduardo Suprinyak, as well as a new general-research essay by Daniel Kuehn, an archival discovery by Katia Caldari and Luca Fiorito, and a book review by John Hall.
Includes index.
Keywords: Economics -- South America -- History.; Economics -- Latin America -- History.; Economics -- South America -- Methodology.; Economics -- Latin America -- Methodology.; South America -- Economic conditions.; Latin America -- Economic conditions.; Business & Economics -- Economic History.; Economic theory & philosophy.; elektronické knihy; electronic books